Faktor-Faktor yang Mempengaruhi Niat Menggunakan E-Filing pada Wajib Pajak Pribadi di Kota Madiun - Andris Krisnawati; Sri Rustiyaningsih; -- Mujilan (JRMA (Jurnal Riset Manajemen dan Akuntansi), 2015)
This research aims to prove in empirical the factors that affect the intention of taxpayers in using e-filing madiun in the city, by using a model of technology model (TAM) modification of acceptance and add gender variables, experience, and kesukarelaan. The population in this research is tax payers in madiun city that has been using e-filing. Who deserves to sample analyzed questionnaires were 44. Data analysis using least partial squares (pls smartpls 2.0.m3). Perceptions of usefulness of research results show no significant to the attitude of perception also use the e-filing uses no effect on the intention of using e-filing. The perception of the ease of significant against the perception of the usefulness of perception also significant to the attitude of the ease of use e-filing. The attitude of using e-filing not significant to the intention of using e-filing .Influential signifi gender.